2012
DOI: 10.1002/art.34660
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional cortico–basal ganglia–thalamic circuit and altered hippocampal–amygdala activity on cognitive set‐shifting in non‐neuropsychiatric systemic lupus erythematosus

Abstract: Objective. To explore sequential brain activities throughout cognitive set-shifting, which is critical to understanding the basic pathophysiology of cognitive dysfunction, in patients with new-onset systemic lupus erythematosus (SLE) without neuropsychiatric symptoms.Methods. Fourteen patients with new-onset SLE but without neuropsychiatric symptoms and 14 healthy controls matched for age, sex, education level, and intelligence quotient with the patients performed a cognitive set-shifting task derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…In addition, the DMN regions were demonstrated to possess the highest structure–function connectivity agreement within the entire brain (Horn et al, 2014). Thus, the structural disruption of the regional topological features in DMN was assumed to be the underlying cause of the decrease in the cognitive function of non-NPSLE and NPSLE patients (Mackay et al, 2011, Ren et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DMN regions were demonstrated to possess the highest structure–function connectivity agreement within the entire brain (Horn et al, 2014). Thus, the structural disruption of the regional topological features in DMN was assumed to be the underlying cause of the decrease in the cognitive function of non-NPSLE and NPSLE patients (Mackay et al, 2011, Ren et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The mean age of 37.6 years was reported for adults, and for children was 15.7 years. Two studies had provided intelligence quotient (IQ) scores for the SLE participants in their study (19,21).…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
“…A summary of the studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) is depicted in Table 1. The largest original study contained 31 participants with SLE, whilst the smallest included 9 patients.…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
“…It has been suggested that blood oxygen level-dependent functional magnetic resonance imaging (BOLD fMRI) is a promising approach to study human cognitive function, which utilizes deoxyhemoglobin as an endogenous contrast agent to identify areas of increased perfusion. Using fMRI, several studies have reported working memory [10], motor control [11], attention and language processing [12], and executive function [13] alterations in SLE patients; however, most of the results obtained in the above fMRI studies were performed with neuropsychiatric SLE (NPSLE) patients, while few studies were designed to characterize brain cognitive function alterations in lupus patients without obvious neuropsychiatric symptoms. Given the high prevalence and poor prognosis for NPSLE, it is meaningful to address whether or not brain dysfunction precedes the evolution of NPSLE in lupus patients without clinically obvious neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%